ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF THE PEEL EXTRACTS OF Luffa acutangula - A. NETHRA and M. POONKOTHAI* (The Journal of Research ANGRAU, 2020)
The study was conducted to evaluate the antimicrobial and phytochemical activities of the peel extracts ofLuffa acutangula. The antimicrobial activity of aqueous, petroleum ether, acetone and chloroform peel extractswas tested against the selected bacterial and fungal isolates using agar well diffusion method. The resultsproved that the acetone extract exhibited maximum antimicrobial activity against the tested bacterial and fungalisolates when compared to chloramphenicol and flucanazole (standard antibiotics) respectively. Preliminaryphytochemical screening was carried out in the acetone extract of L. acutangula which revealed the presenceof secondary metabolites such as saponins, phenols, terpenoids, tannins, flavonoids, sterols, anthocyanin,carbohydrates and amino acids. The FT-IR analysis revealed the presence of hydroxyl, amines and carboxylicacids as functional groups in L. acutangula.